Modified Field's staining-a rapid stain for Trichomonas vaginalis - Afzan, M.Y.; Sivanandam, S.; Kumar, G.S. (Elsevier, 2010)
Trichomonas vaginalis, a flagellate protozoan parasite commonly found in the human genitourinary tract, is transmitted primarily by sexual intercourse. Diagnosis is usually by in vitro culture method and staining with Giemsa stain. There are laboratories that use Gram stain as well. We compared the use of modified Field's (MF), Giemsa, and Gram stains on 2 axenic and xenic isolates of T. vaginalis, respectively. Three smears from every sediment of spun cultures of all 4 isolates were stained, respectively, with each of the stains. We showed that MF staining, apart from being a rapid stain (20 s), confers sharper staining contrast, which differentiates the nucleus and the cytoplasm of the organism when compared to Giemsa and Gram staining especially on parasites from spiked urine samples. The alternative staining procedure offers in a diagnostic setting a rapid stain that can easily visualize the parasite with sharp contrasting characteristics between organelles especially the nucleus and cytoplasm. Vacuoles are more clearly visible in parasites stained with MF than when stained with Giemsa. (C) 2010 Elsevier Inc. All rights reserved.